C.G. Jung and the postmodern discourse - Bytniewski, Jerzy (Hybris, 2016)
Today we cannot say with certainty what the Swiss psychologist attitude towards postmodernism would be, therefore it is reasonable to ask: what are the similarities and differences between the Depth Psychology and the above-mentioned trend? Omitting the underlying absolutism present in the Jung`s “system” (revealing itself in the archetypal construction not only of human world but reality overall (in radically idealistic interpretation of Jung`s philosophy) reveals to us the variety of expressions, that appear to imply a totally different tendency present in his writings. Instead of strengthening unchangeable foundations of reality here we find their dissolution; instead of creating monolithic human psychology we find far-reaching relativization (theoretical and moral); instead of universalistic rules of individual development and precise ethical obligations concerning every human separately, we find vast margin of freedom and great number of equally valuable paths of personality development left to the individual. In the proposed papers I would like to show Jung not as the hypothetical enemy of postmodernism but more as a proto-postmodernist, or perhaps even as a postmodernist par excellence.